Analysis of dehesas with multiple use. Physical and economic indexes of sustainable management - Garcia, F P; SÁNCHEZ, M E; Diaz, F J M; Vega, A R D (BASIS OF THE QUALITY OF TYPICAL MEDITERRANEAN ANIMAL PRODUCTS, 1998)
The wide surface that dehesas hold in Spain, together with their economic, social and environmental importance, give enough justification to the researchs that widen the scientific knowlege about the economics of dehesa systems. However, the dehesa agroforestry farms do not appear in the different statistical documentary sources of the Agricultural Accounting Net. The lack of technical-economic data about these systems impede neither to observe the effects of the Common Agricultural Policy on the natural environment, nor to know as a whole the dynamics and structure of their flows and the stock of resources and income. This paper deals with the technical and economic management of dehesas in the field of the environmental economics. Its main aim has been to carry out an analytical case study. In order to develop it, four dehesa farms in the Southwest of the Badajoz Province were selected. These farms have collaborated on the development of the Research Project UE CAMAR CT 90-28 ``Technical and economic analysis of dehesa and montado systems{''}. Its importance lies in the basis of the case analysis, with a description of the systems and an identification of the structure and dynamics of their resources, either at physical and economic level.
Keywords: Dehesa; environmental econ; sustainable management

Ecological food production from animal origin in the dehesa agrosystem of Andalucia and Extremadura - Mata, C; Caballero, I; Labrador, J; Casco, J M G (BASIS OF THE QUALITY OF TYPICAL MEDITERRANEAN ANIMAL PRODUCTS, 1998)
Andalucia and Extremadura gather certain advantages and conditions for the development of ecological stockbreeding which place them among the European territories of greatest potential in this sense. There are wide areas of high environmental balance, some of them declared as Natural Protected Areas-, with soils of only forestal and silvopastoral use, and with a lot of farms used for the traditional extensive stockbreeding. In this area the management is close to the ecological stockbreeding, and the location coincides with the one of dehesa farms. Most of these farms suffer problems derived from the pressure to which they are subjected because of a management towards greater intensification. Their functions are not valued properly. Many times their products are not competitive with the usual market prices. Being, however of greater organoleptic, sanitary, environmental quality and being even greater, their possibility of profitability. The conversion of extensive stockbreeding farms into a type of ecological production may provide solutions to these problems, favouring a consolidated development; and at the same time, it may encourage an action integrated with other agrarian farms, producing sites of pluriactivity and much more profitability. This work shows a description of the most relevant aspects of extensive stockbreeding productions in relation to its conversion into the ecological production.
Keywords: animal ecological production; Dehesa

Iberian ham - Sabio, E; Fallola, A; Sanabria, C; Vidal-Aragon, M C (BASIS OF THE QUALITY OF TYPICAL MEDITERRANEAN ANIMAL PRODUCTS, 1998)
Iberian dry-cured ham is a meat product elaborated from legs of Iberian pigs. This high quality product has been traditionally elaborated in Spain since ancient times. The production is centred in the Southwest of the Iberian Peninsula where it has a great economic, social, and ecological importance. Iberian dry-cured ham quality depends on the raw matter and the technology employed Raw matter quality depends on intrinsic factors (genotype, age, sex), extrinsic factors (feeding, habitat, management), and the slaughtering conditions. Respecting to genotype. at present it is frequent the employment of cross-breeding mainly with Duroc-Jersey (50% and 75% Iberian). The production system is extensive and has three different periods: preweaning, growing, and fattening, this last being fundamental from a quality viewpoint, establishing three commercial categories: `pienso', `recebo', and `bellota'. This production system causes seasoning in Iberian ham production. The elaboration process of Iberian dry-cured ham consists of four steps: salting, post-salting, drying, and cellar The long lasting of the process (18-24 months) and the high temperatures during the drying period (25-30 degrees C) are distinctive aspects of this technology. As compared to Parma or Serrano dry-cured hams, Iberian ham is characterised by: 1) low salt content, 2) high amount of intramuscular fat, rich in oleic acid, 3) high level of proteolysis and lipolysis, and 4) high amount of volatile compounds, mainly linear, medium-chain aldehydes and ketones. There are three Appellation of Origin: `Dehesa de Extremadura', `Guijuelo' and `Sierra de Huelva', and in the next future will appear `Valle de Pedroches'. The most important producer associations are AECERIBER, ACOREX, and ASICI. There are several research centres where this product is preferentially studied, standing out the Department of Agrofood technology of the Junta de Extremadura and the Veterinary faculty of the University of Extremadura.
Keywords: Extensive system; Iberian ham; raw matter

Production of free range chickens in the Spanish South-west - Duran, A M; Pascual, M R P (BASIS OF THE QUALITY OF TYPICAL MEDITERRANEAN ANIMAL PRODUCTS, 1998)
The object of this study is to elaborate a description of the products obtained from the breeding of free range chickens in the Spanish South-west, considering the possible sex influence. 24 Redstar Shaver chickens were used, 12 males and 12 females chickens. The animals were controlled weekly to determine productive yields when alive. After their slaughter, notes on carcasses and meats were taken. The males weighted more at the slaughter time and presented a better yield of the eviscerated carcass. The females showed a greater abdominal fat content and the regional composition was virtually the same in both sexes, however a greater percentage of legs was found in the males. The dissection of the inferior extremities showed a greater edible meat content in the females chickens. The organoLeptic tests (pH and water holding capacity CRA) presented relevant differences between sexes (greater pH and CRA. in the males). The comparison of the meat nutritive Value (protein and ashes) did not show relevant differences between males and females. This study shows that male and female chickens are products with similar nutritive value but distinguishable by other parameters.
Keywords: Dehesa; extensive chickens; production; Quality meat; sex poultry carcass